2016
DOI: 10.1111/ina.12328
|View full text |Cite
|
Sign up to set email alerts
|

From air to clothing: characterizing the accumulation of semi-volatile organic compounds to fabrics in indoor environments

Abstract: Uptake kinetics of semi-volatile organic compounds (SVOCs) present indoors, namely phthalates and halogenated flame retardants (HFRs), were characterized for cellulose-based cotton and rayon fabrics. Cotton and rayon showed similar accumulation of gas- and particle-phase SVOCs, when normalized to planar surface area. Accumulation was 3-10 times greater by rayon than cotton, when normalized to Brunauer-Emmett-Teller (BET) specific surface area which suggests that cotton could have a longer linear uptake phase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 64 publications
5
59
0
Order By: Relevance
“…The partition coefficients observed here for 100% cotton materials are similar to those reported by Morrison et al and Cao et al for di‐n‐butylphthalate (DnBP; log 10 K vol = 6.6, 6.1), lower than distribution coefficients reported by Saini et al for DnBP, di‐isobutyl phthalate (DiBP), or diethylhexylphthalate (DEHP) (log 10 K vol = 6.8, 7.2, and 7.4, respectively) but higher than those reported for diethylphthalate (log 10 K vol = 5.7) or methamphetamine (log 10 K vol = 5.7) . These, and additional literature data that were reported to be at or near equilibrium, are plotted against the octanol‐air partition coefficient ( K oa ) in Appendix S7 (Figure A.7.1).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The partition coefficients observed here for 100% cotton materials are similar to those reported by Morrison et al and Cao et al for di‐n‐butylphthalate (DnBP; log 10 K vol = 6.6, 6.1), lower than distribution coefficients reported by Saini et al for DnBP, di‐isobutyl phthalate (DiBP), or diethylhexylphthalate (DEHP) (log 10 K vol = 6.8, 7.2, and 7.4, respectively) but higher than those reported for diethylphthalate (log 10 K vol = 5.7) or methamphetamine (log 10 K vol = 5.7) . These, and additional literature data that were reported to be at or near equilibrium, are plotted against the octanol‐air partition coefficient ( K oa ) in Appendix S7 (Figure A.7.1).…”
Section: Discussionsupporting
confidence: 87%
“…In addition to the stable mass accumulated, Log 10 ( K area ) at 7 days ranges over >1 order of magnitude. If the materials were still far from equilibrium, we would anticipate that the area normalized partition coefficients would be similar, that is, the uptake rate during the first 7 days would be similar among samples due to mass‐transport resistance from bulk air to fabric surfaces …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational methods may also allow for estimating partition coefficients for those SVOC‐fabric pairs that have not been investigated experimentally . Goss applied several computational methods to estimate K cellulose‐water and found that their results correlated well with most measurements reported by Hung et al .…”
Section: Discussionmentioning
confidence: 70%
“…As these estimates are based on values obtained in water, the cellulose should be considered "fully hydrated." In air, the cellulose in cotton would be less than fully hydrated and resulting partition coefficients for low-polarity compounds like DEP and DnBP may be somewhat higher.Computational methods may also allow for estimating partition coefficients for those SVOC-fabric pairs that have not been investigated experimentally 29. Goss 30 applied several computational methods to estimate K cellulose-water and found that their results correlated well with most measurements reported by Hung et al28 Note that DEP and DnBP were excluded from their correlation because their predictions deviated significantly from the Hung et al28 results.…”
mentioning
confidence: 93%